Intensitas Pembelajaran Seni Musik melalui Kegiatan Ekstrakurikuler Rebana di Madrasah Ibtidaiyah - Nailissa'adah; Eka Titi Andaryani; Putri Yanuarita Sutikno (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
Music art is one of the subjects of art in Elementary School, Madrasah Ibtidaiyah and equivalent. The limited allocation of time for art subjects which is only 2 hours of lessons per week makes the space narrower for students who want to explore and hone their talents. This study aims to provide an overview of the implementation of extracurricular tambourine activities as one of the forums that accommodate students who want to increase their creativity in the field of religious music arts. The method in this study is descriptive qualitative. The data collection techniques used are observation, interviews and literature studies. The results of this study are that extracurricular tambourine activities in Madrasah Ibtidaiyah are a solution to the lack of time to explore the study of music arts subjects in classroom learning activities. Students who have an interest and tend to have musical intelligence are directed to participate in extracurricular tambourine activities. This activity has a positive value in developing the potential talents and interests of students in the field of music arts, especially Islamic music arts. In addition, this extracurricular activity supports music arts learning in Madrasah Ibtidaiyah.